2015
DOI: 10.1136/bjophthalmol-2014-306547
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary graft survival following penetrating keratoplasty and Descemet's stripping endothelial keratoplasty in eyes with prior trabeculectomy

Abstract: Eyes with prior glaucoma showed higher rates of DSEK graft failure compared with PK. Patients with prior trabeculectomy demonstrated higher and earlier corneal graft failure rates with DSEK than with PK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…These present data support the hypothesis that immune reaction to the intraocular antigen in the first operated eye may cause bleb failure in the second operated eye. Indeed, corneal transplantation graft failure frequently occurs in eyes in which glaucoma filtering surgery has been performed [ 12 ],[ 13 ],[ 14 ]. It is possible that immune communication between the intraocular antigens and the subconjunctival space could cause an adverse effect on the surgical outcome of additional surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These present data support the hypothesis that immune reaction to the intraocular antigen in the first operated eye may cause bleb failure in the second operated eye. Indeed, corneal transplantation graft failure frequently occurs in eyes in which glaucoma filtering surgery has been performed [ 12 ],[ 13 ],[ 14 ]. It is possible that immune communication between the intraocular antigens and the subconjunctival space could cause an adverse effect on the surgical outcome of additional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Eyes in which filtering surgery, including trabeculectomy and tube-shunt surgery, have been performed are at risk for corneal transplantation graft failure [ 12 ],[ 13 ],[ 14 ]. It has been hypothesized that this may be caused by a change in immune status after the creation of a communication between the anterior chamber and the subconjunctival space [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…DSEK has its limitations in complex cases such as in the presence of previous tube shunt procedures, trabeculectomies and previously failed DSEK or penetrating keratoplasty grafts [ 4 8 ]. For patients with tube shunts, the tube placement in the anterior chamber may interfere with the surgical placement of the corneal graft and allow air to escape causing possible graft detachment in the first postoperative day [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic elevation of intraocular pressure compromises the corneal endothelium, leading to accelerated endothelial cell losses, and limits the prognosis and represents a risk factor for graft failure 20 , 22 , 24 ) in cases where cornea transplant has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that increased intraocular pressure is another risk factor for endothelial cell loss after keratoplasty, especially penetrating keratoplasty 20 , 22 , 24 . Glaucoma behaves as a predictor for corneal tissue impairment, both pre and post-transplant.…”
Section: Discussionmentioning
confidence: 99%